Epigenetic mechanisms involved in methamphetamine addiction - Wang, Hang; Dong, Xianghuan; Awan, Maher Un Nisa; Bai, Jie (Frontiers in Pharmacology, 2022)
Methamphetamine (METH) is an illicit psychostimulant widely abused. The molecular mechanism of METH abuse is complicated and still unknown. METH causes the release of the neurotransmitters including dopamine, glutamate, norepinephrine and serotonin, which activate various brain areas in the central nervous system. METH can also lead to synaptic plasticity and pathological memory enhancement. Epigenetics is involved in METH addiction. This paper will briefly summarize the studies on epigenetics related to METH addiction.